STRATEGI PENGEMBANGAN DAN PENGELOLAAN HOMESTAY DI DESA WISATA KULU - Caroles, Krisliana Putri Ema; Lagarense, Bet El SIlisna; Polii, Bernadain D. (HOSPITALITI DAN PARIWISATA, 2025)
This study aims to analyze the development and management strategies of homestays in Kulu TourismVillage as part of efforts to improve service quality and community-based tourism attractiveness. Theresearch employed a qualitative approach with data collection techniques including in-depthinterviews, participatory observation, and documentation. The findings reveal that the developmentstrategies focus on enhancing local human resource capacity through hospitality training, digitalpromotion, and the utilization of local cultural and natural assets. Meanwhile, the managementstrategies emphasize community-based governance, collaboration with village authorities and tourismagencies, and service standardization. Major challenges include limited infrastructure, humanresources, and access to digital marketing. Therefore, a sustainable collaborative approach involvinglocal communities, government, and tourism stakeholders is essential to support homestays as a pillarof the local economy in Kulu Tourism Village